2014
DOI: 10.4236/ajac.2014.59070
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Green, Oolong, and Black Teas by GC-MS Analysis of Characteristic Volatile Flavor Compounds

Abstract: Tea is one of the most consumed beverages in the world and its quality is influenced by geographical origin and production methods. This study focuses on the volatile aroma components of 38 tea products from China, Japan, Indonesia, Sri-Lanka, and Chinese Taipei; among them 7 green teas, 13 oolong teas, and 18 black teas. The volatiles were extracted from the infusions using PorapakQ-resin, concentrated, and analyzed by gas chromatography-mass spectrometry. The components were identified by authentic reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 19 publications
3
48
0
Order By: Relevance
“…2-Furanmethanol (GC5) (a flavouring ingredient) was found in all teas except in the bush-special tea blend. This compound has previously been reported in oolong, green and black tea [22]. 2-Methoxy-4-vinylphenol (GC6) and dihydroactinidolide (GC35) were detected in all tea samples, albeit with slight differences in their relative abundance in the teas.…”
Section: Gc-ms Identification Of Volatile Compounds In Selected Teassupporting
confidence: 70%
“…2-Furanmethanol (GC5) (a flavouring ingredient) was found in all teas except in the bush-special tea blend. This compound has previously been reported in oolong, green and black tea [22]. 2-Methoxy-4-vinylphenol (GC6) and dihydroactinidolide (GC35) were detected in all tea samples, albeit with slight differences in their relative abundance in the teas.…”
Section: Gc-ms Identification Of Volatile Compounds In Selected Teassupporting
confidence: 70%
“…34 Our previous study on comparison of volatiles of green teas, oolong teas, and black teas from different cultivars and regions also proposed that jasmine lactone and indole were characteristic volatiles in oolong tea products. 35 Furthermore, the present study indicated that these volatiles mostly accumulated at the turn over …”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Hereafter, the most significant changes are the rapid conversions and transformations of the precursors to benzylalcohol, indole, safranal, linalool oxides, β -ionone, and hexadecanoic acid methyl ester, mostly by enzymatic catalysis and chemical processes. Therefore, fermentation intensity influences the quantity of most tea volatiles during the manufacturing process of green, oolong and black tea; and because of the distinctive processes of oolong tea, its aroma characteristics are different from the unfermented green or fully fermented black tea (Baldermann et al 2014 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%